2014
DOI: 10.1002/hfm.20610
|View full text |Cite
|
Sign up to set email alerts
|

Agile Enterprise: A Human Factors Perspective

Abstract: The results of the case study showed that the organizational identity includes the attributes that affect the organization's ability to be agile. Comparison of 2 companies, one of which has the characteristics of an agile organization and the other that operates in the traditional manner, showed that the evaluation of these attributes is some kind of a prerequisite for assessing the agility of the organization. This issue may become the next research problem. The article also presents the results of a study co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…Recently a broad range of IS researchers (Sambamurthy et al, 2003;Overby et al, 2006;Rai et al, 2006;Tallon, 2008;Lu and Ramamurthy, 2011;Tallon and Pinsonneault, 2011;Nazir and Pinsonneault, 2012;Cai et al, 2013;Chen et al, 2014;Mao et al, 2014;Chen et al, 2015;Mao et al, 2015;Ragin-Skorecka, 2016) have shown an immense interest on the concept of "agility". For example, according to Chen et al (2015) and Mao et al (2014), organizational agility delineates the competency with which a firm deals with imminent market uncertainties by means of innovative and rapid responses which transform these market changes into opportunities.…”
Section: Literature Review and Hypotheses Building 21 Organizational Agilitymentioning
confidence: 99%
“…Recently a broad range of IS researchers (Sambamurthy et al, 2003;Overby et al, 2006;Rai et al, 2006;Tallon, 2008;Lu and Ramamurthy, 2011;Tallon and Pinsonneault, 2011;Nazir and Pinsonneault, 2012;Cai et al, 2013;Chen et al, 2014;Mao et al, 2014;Chen et al, 2015;Mao et al, 2015;Ragin-Skorecka, 2016) have shown an immense interest on the concept of "agility". For example, according to Chen et al (2015) and Mao et al (2014), organizational agility delineates the competency with which a firm deals with imminent market uncertainties by means of innovative and rapid responses which transform these market changes into opportunities.…”
Section: Literature Review and Hypotheses Building 21 Organizational Agilitymentioning
confidence: 99%
“…An agile organization can rapidly adapt all enterprise elements such as goals, technology, organization, and people to the unpredicted and unexpected changes (Kidd, 1994). Agility refers to the ability of employees to use market knowledge and virtual structure for exploiting profitable opportunities in volatile marketplace (Agarwal, Shankar, & Tiwari, 2006;Lin, Chiu, & Tseng, 2006;Naylor, Naim, & Berry, 1999;Ragin-Skorecka, 2014). Fliedner and Vokurka (1997) defined agility as a successful marketing capability of low-cost qualified products in various quantities at relatively short waiting time that makes more profit for customers.…”
Section: Organizational Agilitymentioning
confidence: 99%
“…A third factor included in many definitions of organizational agility is learning and constantly building up skills, knowledge, and experience. This is emphasized given the need for constant renewal in an agile organization and the necessity to adapt existing competencies to fit an ever-changing environment and to design and develop new capabilities (Ragin-Skorecka, 2016;Weber & Tarba, 2014;Winby, & Worley, 2014). Finally, it is noteworthy that especially the practitioner literature emphasizes a network structure, a people-centered and purpose-driven culture, and iterative processes to refine a product as trademarks of an agile organization (Aghina et al, 2017;Eilers et al, 2018).…”
Section: Agile Organizationsmentioning
confidence: 99%